Trilogi Kepemimpinan Ki Hajar Dewantara - Leo Agung S. (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Leadership is an ability or strength within a person to lead and influence others in terms of work, with the aim of achieving predetermined targets. A leader is someone who is entrusted with being the chairman (head) of a system in an organization/institution/company. Thus, a leader must have the ability to guide and influence a person or group of people. In the Javanese concept, the ideal leadership is a leader who masters the science of Hasta Brata, namely a leader who has natural characteristics that represent a symbol of the wisdom and greatness of the Creator, namely; the nature of the Earth, the nature of the Sun, the nature of the Moon, the nature of the Ocean, the nature of the Stars, the nature of the Wind, the nature of Fire, and the nature of Water. From Hasta Brata, then by Ki Hajar Dewantara abstracted into the Leadership Trilogy, namely "Ing ngarsa sung tulodho, Ing madya mangun karso, Tut wuri handayani".